CCL2 is Modulated by Cytokines and PPAR-γ in Anaplastic Thyroid Cancer - Ferrari, Silvia M.; Elia, Giusy; Piaggi, Simona; Baldini, Enke; Ulisse, Salvatore; Miccoli, Mario; Materazzi, Gabriele; Antonelli, Alessandro; Fallahi, Poupak (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background and Objective: Chemokine (C-C motif) ligand (CCL)2, the prototype Th2 chemokine, is secreted by tumor cells, and has growth promoting effects. Whether CCL2 protumorigenic activities will be validated, then CCL2 and its receptor CCR2 may be therapeutic targets in cancer. Methods: We tested in “primary human anaplastic thyroid carcinoma (ATC) cells” (ANA) versus “normal thyroid follicular cells” (TFC): a) CCL2 secretion basally, after IFN-γ and/or TNF-α stimulation; b) PPARγ activation by thiazolidinediones (TZDs), rosiglitazone or pioglitazone, on CCL2 secretion, and on proliferation and apoptosis in ANA. Results: ANA produced basally CCL2, at a higher level versus TFC. IFN-γ or TNF-α dose-dependently induced the CCL2 release in 3/6 or 5/6 ANA, respectively, but in all TFC. IFN-γ+TNF-α induced a synergistic release of CCL2 in all TFC, but only in 1/6 ATC. TZDs exerted an inhibition of CCL2 release in 3/6 ANA, while had no effect in TFC. Pioglitazone inhibition of ANA proliferation was not associated with the effect on CCL2; NF-ΚB and ERK1/2 were basally activated in ANA, increased by IFN-γ+TNF-α, and pioglitazone inhibited IFN- γ+TNF-α activation. CCL2 serum levels were higher in 6 ATC patients than in 5 controls (813±345 versus 345±212, pg/mL; respectively; P<0.01, ANOVA). Conclusion: ANA produce CCL2 basally and after cytokines stimulation, with an extremely variable pattern of modulation, suggesting different types of deregulation in the chemokine modulation. Serum CCL2 is increased in ATC patients. Further studies will be necessary to evaluate if CCL2 might be used as a marker in the followup of ATC patients.
Keywords: PPAR-γ